Review: Saldanha, Camila Teixeira; Laiño, Maria José; Melo, Noemi Teles; Pontes, Valdecy de Oliveira (orgs.). Tradução funcionalista no Brasil: perspectivas teóricas e aplicadas ao ensino de línguas. Curitiba: Editora CRV, 2020. 158 p.: Review: Saldanha, Camila Teixeira; Laiño, Maria José; Melo, Noemi Teles; Pontes, Valdecy de Oliveira (orgs.). Tradução funcionalista no Brasil: perspectivas teóricas e aplicadas ao ensino de línguas. Curitiba: Editora CRV, 2020. 158 p. - Teodósio do Nascimento, Erika (2022)
N/A